Core competency of the M.Sc. (epizootiology) programme at the University of Ibadan, Ibadan, Nigeria (2006)
The concept of Core Competence developed to assess professional training needs, was applied in this 2004 study to evaluate the Masters of Science (Epizootiology) programme developed in 1984 at the Department of Veterinary Public Health and Preventive Medicine, Faculty of Veterinary Medicine, University of Ibadan. Ibadan, Nigeria. Results indicate the curricular covered four of the five major Core Competency needs in Epizootiology (Veterinary Epidemiology), with sufficient curricular courses available for General Skills, Surveillance and Monitoring Skills, Outbreak Investigation Skills as well as Study Design and Analysis. There are however major deficiencies in the fifth core subject of Risk Analysis. In addition to including the socio-economic concept of risk analysis, there is a review of the Masters of Epizootiology curricular of the University of Ibadan to harness all concepts within the fundamental nature of epizootiology; from the traditional long-established macroscopic field-based Participatory Epizootiology/Ethno-Veterinary Medicine perception of the stakeholder rural livestock farmer, to promoting modern contemporary microscopic desk/laboratory epizootiological concepts of Risk Assessment, Genetic and Molecular Biology, Geographic Information System and other Veterinary Computer Informatics facilities. However, field-based observational and descriptive studies remain the basis of epizootiological training and investigation.